The Effectiveness of the Shuffle and Recall Game on Arabic Vocabulary Mastery Among Tenth-Grade Students - Haikal Akhtar Haniff; Salma Ubaidah; Rina Asih Handayani; Nurdina binti Razlan (Jurnal Ilmiah Global Education, 2026)
This study aimed to determine the effectiveness of utilizing the Shuffle and Recall game, a component of the Clash of Champions program, on the Arabic vocabulary mastery among tenth-grade students at MAN 1 Semarang City. The underlying phenomenon was the low level of Arabic vocabulary proficiency among high school students, which is often attributed to the dominance of less interactive conventional teaching methods and the perception that Arabic is a difficult language to learn. The research method employed a quasi-experimental design featuring a pretest-posttest control group. The research population comprised all tenth-grade students at MAN 1 Semarang City during the 2024/2025 academic year, totaling 350 students. The results indicated a significant increase in scores within the experimental class. Prior to the intervention, the average pretest scores for both classes were relatively similar or homogeneous (Experimental: 64.57; Control: 63.71). Conversely, the posttest results demonstrated a significant difference, with the average posttest score for the experimental class reaching 84.29, while the control class achieved 72.86. The conclusion is that the Shuffle and Recall game proved to be an effective tool for improving the Arabic vocabulary mastery of tenth-grade students at MAN 1 Semarang City. This game facilitates active learning, enhances short-term and long-term memory through retrieval practice, and fosters increased student learning motivation.